2019
DOI: 10.1242/jcs.223313
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 maintains tissue polarity and regulates mitotic spindle orientation in the breast epithelium

Abstract: Cell-cell communication is essential for tissue homeostasis, but its contribution to disease prevention remains to be understood. We demonstrate the involvement of connexin 43 (Cx43, also known as GJA1) and related gap junction in epithelial homeostasis, illustrated by polarity-mediated cell cycle entry and mitotic spindle orientation (MSO). Cx43 localization is restricted to the apicolateral membrane of phenotypically normal breast luminal epithelial cells in 3D culture and in vivo. Chemically induced blockad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 117 publications
10
64
0
Order By: Relevance
“…Consistent with our in vivo findings that suppression of Cx43 increases strial BLB permeability, downregulation of Cx43 in vitro also made the EC monolayers more permeable. Our results are consistent with recent reports on non-auditory systems, in which Cx43 affects TJ formation and loss of Cx43 leads to blood barrier hyper-permeability (Hollenbach et al, 2018;Johnson et al, 2018;Bazzoun et al, 2019). The mechanism by which suppression of Cx43 alters TJ organization was not determined in this study, and, in fact, the mechanism by which suppression of Cx43 alters TJ organization is largely unknown.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our in vivo findings that suppression of Cx43 increases strial BLB permeability, downregulation of Cx43 in vitro also made the EC monolayers more permeable. Our results are consistent with recent reports on non-auditory systems, in which Cx43 affects TJ formation and loss of Cx43 leads to blood barrier hyper-permeability (Hollenbach et al, 2018;Johnson et al, 2018;Bazzoun et al, 2019). The mechanism by which suppression of Cx43 alters TJ organization was not determined in this study, and, in fact, the mechanism by which suppression of Cx43 alters TJ organization is largely unknown.…”
Section: Discussionsupporting
confidence: 92%
“…In morphogenesis, connexins are indispensable for coordinated tissue growth (Sinyuk et al, 2018). By regulating cell differentiation, connexins further counteract neoplastic transformation Fostok et al, 2019;Saunders, 2001;Zhang et al, 2003) and forced expression of connexins in transformed cells reduces tumor cell growth and inhibits invasion by reverting the epithelial-to-mesenchymal transition (Kazan et al, 2019;McLachlan et al, 2006). On the other hand, connexins remain expressed in several solid tumors and expression increases in metastases (Bos et al, 2009;Elzarrad et al, 2008;Kanczuga-Koda et al, 2006;Stoletov et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For breast cancer, obesity is one of the few modifiable risk factors and is characterized by a chronic state of inflammation and deregulation of cytokine and growth factors in circulation (33,34). Our group found that cell microenvironments characteristic of obesity lead to the mislocalization of apical polarity proteins and premalignant changes in the mammary gland (14,35). Apical polarity was also found to be disrupted by omega-6 fatty acids, which may be associated with increased breast cancer risk (36).…”
Section: Epithelial Polarity For Breast Cancer Risk Assessmentmentioning
confidence: 94%
“…GJs consist of connexons (connexin hexamers) and are classically represented toward the basal side of epithelial cells. Yet connexin 43 was recently found to be apically localized in the breast epithelium, and to be required for apical polarity establishment and maintenance (14).…”
Section: Introduction Epithelial Polarity In the Normal Mammary Glandmentioning
confidence: 99%